2019
DOI: 10.1038/s41598-019-41414-8
|View full text |Cite
|
Sign up to set email alerts
|

Low survival rate and muscle fiber-dependent aging effects in the McArdle disease mouse model

Abstract: McArdle disease is an autosomal recessive disorder caused by the absence of the muscle glycogen phosphorylase, which leads to impairment of glycogen breakdown. The McArdle mouse, a model heavily affected by glycogen accumulation and exercise intolerance, was used to characterize disease progression at three different ages. The molecular and histopathological consequences of the disease were analyzed in five different hind-limb muscles (soleus, extensor digitorum longus, tibialis anterior, gastrocnemius and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…However, the generated mouse model has some disadvantages, such as much higher glycogen accumulation in muscles than observed in patients, because of faster metabolic rates in mice. Additionally, the mouse McArdle model shows a high level of perinatal and post-weaning mortality [ 75 ]. It was also observed that the glucose metabolism pathways, which were activated to compensate for the lack of PYGM, are different in the mouse model and humans affected by McArdle disease [ 76 , 77 ].…”
Section: Why Use Zebrafish To Study Pygm?mentioning
confidence: 99%
“…However, the generated mouse model has some disadvantages, such as much higher glycogen accumulation in muscles than observed in patients, because of faster metabolic rates in mice. Additionally, the mouse McArdle model shows a high level of perinatal and post-weaning mortality [ 75 ]. It was also observed that the glucose metabolism pathways, which were activated to compensate for the lack of PYGM, are different in the mouse model and humans affected by McArdle disease [ 76 , 77 ].…”
Section: Why Use Zebrafish To Study Pygm?mentioning
confidence: 99%
“…McArdle (PYGM R50X/R50X ) and representative wild-type (PYGM wt/wt ) mice were generated on a C57BL/6 background and extensively characterized as previously described (27,28).…”
Section: Animals and Ethical Approvalmentioning
confidence: 99%
“…To investigate the effects of SFe on different muscle types, TA muscle was stained with PAS. PAS can differentiate oxidative red (slow twitch) fibers from glycolytic white (fast twitch) fibers according to glycogen content [2022]. The number of oxidative red fibers did not differ between the 20M and 16M CON groups but was significantly increased in the 20M SFe group compared with the 20M CON group (Figures 3(b) and 3(e)).…”
Section: Resultsmentioning
confidence: 99%